Quantitative Limits on Small Molecule Transport via the Electropermeome — Measuring and Modeling Single Nanosecond Perturbations - Esin B. Sözer (Nature Portfolio, 2017)
Abstract The detailed molecular mechanisms underlying the permeabilization of cell membranes by pulsed electric fields (electroporation) remain obscure despite decades of investigative effort. To advance beyond descriptive schematics to the development of robust, predictive models, empirical parameters in existing models must be replaced with physics- and biology-based terms anchored in experimental observations. We report here absolute values for the uptake of YO-PRO-1, a small-molecule fluorescent indicator of membrane integrity, into cells after a single electric pulse lasting only 6 ns. We correlate these measured values, based on fluorescence microphotometry of hundreds of individual cells, with a diffusion-based geometric analysis of pore-mediated transport and with molecular simulations of transport across electropores in a phospholipid bilayer. The results challenge the “drift and diffusion through a pore” model that dominates conventional explanatory schemes for the electroporative transfer of small molecules into cells and point to the necessity for a more complex model.